2014
DOI: 10.1586/1744666x.2014.967684
|View full text |Cite
|
Sign up to set email alerts
|

The importance of TSLP in allergic disease and its role as a potential therapeutic target

Abstract: Thymic stromal lymphopoietin (TSLP) is an epithelial-derived cytokine similar to IL- 7, whose gene is located on chromosome 5q22.1 and it exerts its biological function through the TSLP-Receptor (TSLP-R). TSLP is expressed primarily by epithelial cells at barrier surfaces such as the skin, gut and lung in response to danger signals. Since it was cloned in 1994, there has been accumulating evidence that TSLP is crucial for the maturation of antigen presenting cells and hematopoietic cells. TSLP genetic variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
1
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(136 citation statements)
references
References 143 publications
6
116
1
10
Order By: Relevance
“…In this sense, a high level of IL-13 in asthmatic patients has been involved in wall remodeling processes [76,77]. Moreover, some genetic variants of TSLP have been linked to asthma or allergic rhinitis [78]. The altered genes that appeared in exposed individuals have been implicated in pulmonary effects driven by environmental agents such as viruses, cigarette smoke, oxidants, and air pollution [79][80][81], explaining, in part, the higher susceptibility of these patients to the action of airborne insults (see below).…”
Section: Airway Epithelium As a Key Player In Orchestrating The Allermentioning
confidence: 99%
“…In this sense, a high level of IL-13 in asthmatic patients has been involved in wall remodeling processes [76,77]. Moreover, some genetic variants of TSLP have been linked to asthma or allergic rhinitis [78]. The altered genes that appeared in exposed individuals have been implicated in pulmonary effects driven by environmental agents such as viruses, cigarette smoke, oxidants, and air pollution [79][80][81], explaining, in part, the higher susceptibility of these patients to the action of airborne insults (see below).…”
Section: Airway Epithelium As a Key Player In Orchestrating The Allermentioning
confidence: 99%
“…It is now well recognized that epithelial-derived mediators such as TLSP and IL-33 are critically involved in the development and chronicity of allergic airway disease. [5][6][7] In COPD airway, inflammation is mainly induced by inhaled cigarette smoke or other noxious particles. The pathological changes are found in the airways, lung parenchyma, and pulmonary vasculature.…”
mentioning
confidence: 99%
“…TSLP is overexpressed in the skin stratum corneum, and its expression correlates with the severity of the AD index score and epidermal barrier function, such as stratum corneum hydration and transepidermal water loss [12]. In fact, TSLP appears to be a key cytokine for the progression of the atopic march (atopic dermatitis to asthma), and treatment with anti-TSLP compounds is expected to have important clinical effects [13]. Our study showed that heat-killed S. aureus (HKSA) increased both mRNA and protein expression of TSLP and proinflammatory cytokine IL-6, which is consistent with the clinical finding that AD aggravation can be caused by S. aureus.…”
Section: Discussionmentioning
confidence: 99%